Selective Gas Adsorption of Alkane/Alkene in a Single-Crystal and Powder Bimetallic Metal-Organic Framework Compound Cu2.97Zn0.03(btc)2 Studied by Electron Paramagnetic Resonance - Kultaeva, Anastasia; Böhlmann, Winfried; Hartmann, Martin; Biktagirov, Timur; Pöppl, Andreas (Journal of Physical Chemistry C, 2019)
The metal-organic framework HKUST-1 is an attractive material for gas storage and gas separation applications because of its large surface area and high pore volume, and the presence of coordinatively unsaturated (cus) cupric ion sites. We investigated the interaction of alkenes and alkanes (ethene, 1-butene, ethane, and butane) with Cu2+ ions in their Zn-doped variant Cu2.97Zn0.03(btc)2 by continuous-wave electron paramagnetic resonance spectroscopy. Powder and single-crystal experiments revealed a characteristic change of cupric ion coordination from square planar to square pyramidal for the adsorption of ethylene and 1-butene and confirmed the formation of adsorption complexes at the cus sites of the Cu2+ ion in the mixed metal ion Cu-Zn paddle wheel (PW) units. Quantum chemical calculations based on density functional theory established a weak specific interaction between alkene π-orbitals and Cu2+ ions in a side-on coordination geometry. In contrast, no direct interaction between alkanes and the metal ions was found for this porous material. However, adsorption of ethane and n-butane leads to significant strain effects in the HKUST-1 framework which can be indirectly sensed by the cupric ions in the paramagnetic Cu-Zn PW units.
CRIS-Team Scopus Importer:2019-11-08